Avaliacao dos princípios tacticos em jovens futebolistas de diferentes idades - da Costa, I. T.; Garganta, J.; Greco, P. J.; Mesquita, I.; Afonso, J. (Revista Portuguesa de Ciências do Desporto, 2010)
The aim of this study was to analyze tactical behaviours performed by youth soccer players of different age groups according to ten core tactical principles of the game, in order to understand characteristics of each age group and their differences. The sample comprised a total of 300 youth soccer players (60 U11, 60 U13, 60 U15, 60 U17 and 60 U20), who have performed 17,239 tactical actions. Three tactical measures were analyzed (number of tactical actions, efficiency of tactical behaviours and tactical performance indices). Kruskal-Wallis H and Whitney U tests were applied to compare the values of tactical measures. Data reliability was assured by the Kappa of Cohen index. The results indicated forty statistical differences relative to the number of tactical actions performed, thirty-two statistical differences regarding the efficiency of tactical behaviours, and twenty statistical differences concerning tactical performance indices. In conclusion, one can conclude that as the age group increased, the players had a greater participation in the game, namely by performing of more tactical actions. In addition, the U15 and U17 groups presented no statistical differences in the efficiency of their tactical behaviours, while the U17 and U20 groups exhibited the biggest differences in the tactical performance indices.